Expansion of myeloid-derived suppressor cells with arginase activity lasts longer in aged than in young mice after CpG-ODN plus IFA treatment - Harman, María Florencia (2015)
As we age, the homeostatic function of many systems in the body, such as the immune function declines, which in turn contributes to augment susceptibility to disease. Here we describe that challenging aged mice with synthetic oligodeoxynucleotides containing unmethylated cytosine guanine motifs (CpG-ODN) emulsified in incomplete Freund's adjuvant (IFA), (CpG-ODN+IFA) an inflammatory stimulus, led to the expansion of CD11b+Gr1+ myeloid cells with augmented expression of CD124 and CD31. These myeloid cells lasted longer in the spleen of aged mice than in their younger counterparts after CpG-ODN+IFA treatment and were capable of suppressing T cell proliferative response by arginase induction. Myeloid cells from aged CpG-ODN+IFAtreated mice presented increased arginase-1 expression and enzyme activity. In addition, we found a different requirement of cytokines for arginase induction according to mice age. In myeloid cells from young treated mice, arginase-1 expression and activity is induced by the presence of each IL-4 or IL-6 in their extracellular medium, unlike myeloid cells from aged treated mice which need the presence of both IL-4 and IL-6 together for arginase induction and suppressor function.